PRODUCTION OF CELLULOLYTIC ENZYMES FROM TRICHODERMA SP. STRAINS FOR FERMENTATION OF GRAPE RESIDUES AS SOLID SUBSTRATE REUSING WINE RESIDUES - Solange Grace Barrios Gutiérrez (2021)
Currently, the agri-food society increases waste to the environment with potential environmental impacts and one of them is the wine industry, generating organic waste in short periods, showing that the use of fertilizers in the vineyard, packaging materials, and their waste management suchas grape production in wineries and wine production are responsible for environmental impacts that are highly polluting. In this aspect, grape extracts and grape pomace are rich sources of polyphenols, so in the present study, we evaluated the obtaining of cellulolytic enzymes, through fermentation in solid-state (FES) with strains of Trichoderma sp. Grape pomace and grape stalk residues were used, also Carboxymethylcellulose (CMC) at 0.5 % and mineral solution were added to the (FES). The results showed that grape stalk is a better substrate than grape pomace. In addition, the enzyme activity with (CMC) 0.5 % was 0.1289 U/mL and with saline solution was 0.1286 U/mL. Therefore, it is concluded that cellulolytic enzymes can be obtained by (FES) from grape stalk supplemented with CMC 0.5 %. These results provide relevant data on the regression coefficients to the experimental data resulting in the high potentiality of cellulase production about fungal growth and its enzymatic secretion.